'Don't Think of Fukushima!': The Ethics of Risk Reframing in 'Nuclear for Climate' Communications. Issue 2 (4th May 2021) - Katz-Rosene, Ryan M.
ABSTRACT: In recent years an assemblage of nuclear energy proponents has coalesced around the notion of 'Climate First' – arguing that nuclear power is a necessary component of the fight against climate change. One noteworthy addition to the Climate First fold is the semi-formalized communications campaign Nuclear for Climate (N4C). This article builds upon a previous ethical critique of Climate First by conducting a comparison of the extent of risk concept disclosure seen within N4C's key messaging and more 'traditional' Climate First texts. The article demonstrates how there has been a noticeable shift in the communications strategy of N4C vis-à-vis 'traditionalists', and moreover that models of environmental framing and affective heuristics help to explain the strategic value of this risk reframing for the nuclear industry. It further argues that this reframing of risk gives rise to an ethical paradox, wherein strategic advocates of nuclear energy as a climate mitigation tool could be compelled to withhold important aspects of the nuclear story from the public to promote what they understand to be an urgently-needed tool for saving the planet.